Budget forecast in culture and sports of local governments for sustainable tourism department of La Libertad - Gonzales Espino, David (2022)
Public budget forecasts must be viewed objectively, although it is true that all functions in municipalities are important, we must take into account that it is necessary to establish a consensual analysis of reality for the culture and sports sector. The objective of the research was to identify the forecast of public budgets for the coming years at the level of culture and sports function in the twelve provincial municipalities of the 12 provinces that make up the department of La Libertad. Likewise, sustainable tourism has a direct relationship with culture and plays an important role through economic, environmental and social promotion that is related to culture. Regarding the study method, it has a quantitative approach, a type of basic research and a non-experimental research design of a transectional nature. The results of the forecast through the Winters method determine that there is a heterogeneity in the trend of the budgets, ghlighting the projections for the year 2029 in S/23,929,906 million with a tendency to rise in 2030 with S/35,408,933, then drop in 2031 to S/ 33,146,626 continues to drop in 2032 to S/27,191,223 and rises in 2033 to S/29,991,612. It is important that the user and supply areas become aware of the importance of culture as a proposal for an economic model, through the enhancement of cultural heritage as a pillar of social cohesion and a source of work for the entrepreneurs of the territory.